Germanium-regulated silicon / carbon fiber composite material as well as preparation method and application thereof
Through electrospinning technology and heat treatment steps, a germanium siloxane/carbon fiber composite material with a three-dimensional core-shell structure was prepared, solving the electrode cracking and capacity attenuation caused by volume changes in the negative electrode material of lithium-ion batteries during the lithiation/delithation process. , achieving lithium storage performance with high specific capacity and long cycle stability.
Patent Information
- Application Number
- CN202411527247.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The negative electrode materials of lithium-ion batteries, silicon and germanium, will undergo severe volume changes during the lithiation/delithation process, resulting in electrode cracking, failure and capacity attenuation.
Through electrospinning technology and heat treatment steps, germanium silicerostatic/carbon fiber composite materials (Si/Ge@CNFs) with three-dimensional core-shell structure are prepared. This material evenly distributes silicon nanoparticles and germanium nanoparticles in the carbon fiber matrix to relieve the Problems of volume expansion and poor conductivity.
The composite material exhibits excellent lithium storage performance in the negative electrode of lithium-ion battery, including high specific capacity, long cycle stability and good rate performance, and is suitable for high-performance battery needs in commercial equipment such as electric vehicles.
Smart Images

Figure CN119480960A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a germanium-regulated silicon / carbon fiber composite material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in power supply for electric vehicles and portable devices due to their high energy density, environmental friendliness and long life. In the past decade, fourth group elements have been regarded as attractive alternatives to commercial graphite in lithium-ion battery anodes due to their high theoretical capacity. Among them, the theoretical capacity of silicon is as high as 3579 mAh g -1 , low operating voltage, and abundant reserves make it a preferred candidate for negative electrode materials. However, silicon's inherent low electronic conductivity, ion diffusion capacity, and significant volume expansion have hindered its further development as a negative electrode material for lithium-ion batteries. In addition, germanium is not only attractive for its high capacity, but also exhibits better rate performance and cycle performance due to its good electronic conductivity and fast lithium ion mobility. However, the high price and low abundance of germanium have hindered its commercialization.
[0003] Compared with pure silicon electrodes, the Ge / Si structure has many advantages: first, Ge doping into Si can accelerate the transfer kinetics of lithium, thereby improving the rate performance; second, Si and Ge have different reaction starting potentials with lithium, so they do not expand at the same time, allowing for gradual release of strain stress; finally, when lithium is inserted into one of the components, the other component can act as a buffer to mitigate the volume change. However, despite these advantages, some issues remain to be addressed. During the lithiation / delithiation process, both Si and Ge undergo severe volume changes, which can lead to cracking, failure, and eventual capacity decay of the negative electrode. Designing complex nanostructures with additional free space to accommodate volume expansion is an effective strategy to maintain the structural integrity and cycling stability of the electrode.
[0004] To overcome these challenges, new preparation technologies need to be developed to improve production efficiency and reduce energy consumption. At the same time, in-depth research on the Ge / Si structure is needed to further improve its cycle stability and capacity. This includes exploring a more suitable Ge / Si ratio, optimizing the design of nanostructures, and developing new carbon sources. It is expected to bring progress to the negative electrode materials of lithium-ion batteries and meet the demand for high-performance batteries for commercial equipment such as electric vehicles. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a germanium-regulated silicon / carbon fiber composite material and its preparation method and application. The method successfully prepares a Si / Ge@CNFs composite material with a three-dimensional core-shell structure through simple electrospinning technology and heat treatment steps. The composite material combines the high capacity of silicon and the excellent conductivity of germanium, and effectively buffers the problems of volume expansion and poor conductivity through carbon nanofibers, showing excellent lithium storage performance, and can be used as a negative electrode material for lithium-ion batteries.
[0006] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:
[0007] A method for preparing a germanium-regulated silicon / carbon fiber composite material comprises the following steps:
[0008] Step 1, Preparation of GeO2 / Si dispersion
[0009] Dissolve F127 in deionized water to prepare F127 solution, add GeO2 polycrystalline particles while stirring, and continue stirring at room temperature for 1 hour to obtain a transparent GeO2 / F127 dispersion;
[0010] P123 is dissolved in deionized water, and Si nanoparticles are added to the P123 solution to obtain a Si / P123 dispersion;
[0011] Then, the GeO2 / F127 dispersion is added to the Si / P123 dispersion to obtain a GeO2 / Si dispersion, wherein the molar ratio of Ge to Si is 0.25-2:1;
[0012] Step 2, preparation of GeO2 / Si@PVA fiber composite material
[0013] 0.5 g of sucrose was added to the GeO2 / Si dispersion, and then stirred continuously on a heated stirrer for 2 h, and then 2 g of PVA was added under strong stirring, and the mass ratio of sucrose to PVA was ≥ 0.25:1 (sucrose maintained the fiber morphology after calcination), and then stirred for 12 h to obtain a GeO2 / Si@PVA slurry as an electrospinning liquid, and then electrospinning was performed to obtain a GeO2 / Si@PVA fiber composite material;
[0014] Step 3, Preparation of Ge / Si@CNFs composites
[0015] The GeO2 / Si@PVA fiber composite material was pre-oxidized in air at 150°C for 2 h, then carbonized and reduced in a hydrogen-argon atmosphere, and naturally cooled to room temperature to obtain the Ge / Si@CNFs composite material.
[0016] As an improvement, the concentration of the F127 solution in step 1 is 4wt%, and the concentration of the P123 solution is 1.5wt%.
[0017] As an improvement, the molar ratio of Ge to Si in step 1 is 1:1.
[0018] As an improvement, the mass ratio of (Ge+Si) to PVA in step 2 is 0.5:20-2:20.
[0019] A further improvement is that the mass ratio of (Ge+Si) to PVA in step 2 is 1:20.
[0020] As an improvement, the heating rate of carbonization in hydrogen-argon atmosphere in step 3 is 3°C / min, the carbonization temperature is 800°C, and the reduction time is 6h.
[0021] The germanium-regulated silicon / carbon fiber composite material prepared by the above preparation method includes silicon nanoparticles, germanium nanoparticles and a carbon fiber matrix, wherein the silicon nanoparticles and germanium nanoparticles are uniformly distributed in the carbon fiber matrix to form a three-dimensional core-shell structure.
[0022] The above-mentioned Ge / Si@CNFs composite material is used as a negative electrode material in lithium-ion batteries.
[0023] Beneficial effects:
[0024] Compared with the prior art, the germanium-regulated silicon / carbon fiber composite material and its preparation method and application in the present invention have the following advantages:
[0025] Beneficial effects:
[0026] 1. Structural advantages: The Ge / Si@CNFs composite material prepared by the present invention has a three-dimensional core-shell structure. Based on the different initial reaction potentials of silicon and germanium, and the silicon and germanium nanoparticles are uniformly coated in carbon nanofibers, the stress caused by volume change can be effectively released, and the carbon fibers can alleviate the volume expansion of silicon and germanium.
[0027] 2. Excellent performance: The Ge / Si@CNFs composite material of the present invention combines the high capacity of silicon and the excellent conductivity of germanium. At the same time, its structure can alleviate volume expansion and show excellent lithium storage performance, such as high specific capacity, long cycle stability and good rate performance.
[0028] 3. Simple method: The Ge / Si@CNFs composite material of the present invention uses water as solvent and PVA as spinning polymer. The preparation method is simple, efficient, and low-cost, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the XRD spectrum of the Si / Ge@CNFs composite material prepared in Example 1.
[0030] Figure 2 This is the Raman spectrum of the Si / Ge@CNFs composite material prepared in Example 1.
[0031] Figure 3 This is the thermogravimetric curve of the Si / Ge@CNFs composite material prepared in Example 1.
[0032] Figure 4 This is the SEM image of the GeO2 / Si@PVA fiber composite material prepared in Example 1.
[0033] Figure 5 This is the SEM image of the Si / Ge@CNFs composite material prepared in Example 1.
[0034] Figure 6 TEM image of the Si / Ge@CNFs composite material prepared in Example 1.
[0035] Figure 7 CV curve of Si / Ge@CNFs composite material prepared in Example 1 in LIBs.
[0036] Figure 8 This is the charge and discharge curve of the Si / Ge@CNFs composite material prepared in Example 1 in LIBs.
[0037] Fig. 9 0.2Ag prepared in Example 1 -1 Cycling performance of Si / Ge@CNFs composites under different current densities.
[0038] Fig.10 This is the rate performance of the Si / Ge@CNFs composite material prepared in Example 1 at different current densities.
[0039] Fig.11 0.5A g prepared in Example 1 -1 Long-term cycling performance of Si / Ge@CNFs composites at different current densities.
[0040] Fig.12 Composite materials prepared under different parameters as negative electrode materials at 0.2Ag -1 Cycling performance at different current densities.
[0041] Fig.13 This is the SEM image of the Ge / Si@CNFs-0.05 composite material prepared in Example 2.
[0042] Fig.14 This is the SEM image of the Ge / Si@CNFs-0.15 composite material prepared in Example 3.
[0043] Fig.15This is the SEM image of the Ge / Si@CNFs-0.2 composite material prepared in Example 4.
[0044] Fig.16 This is the SEM image of the Ge@CNFs composite material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0045] Example 1
[0046] The preparation method of Ge / Si@CNFs composite material comprises the following steps:
[0047] (1) Preparation of GeO2 / Si dispersion:
[0048] 0.8 g F127 was dissolved in 20 mL deionized water and stirred for 1 h at room temperature to prepare a 4 wt% F127 solution. Under strong stirring, 0.09 g GeO2 polycrystalline particles were added to the F127 solution and stirred for 1 h at room temperature to obtain a transparent GeO2 / F127 dispersion.
[0049] 0.3 g of P123 was dissolved in 20 mL of deionized water, and 0.0375 g of Si nanoparticles were added to the P123 solution to prepare a Si / P123 dispersion.
[0050] The mixture was ultrasonically treated for 3 h, and then the GeO2 / F127 dispersion was added to the Si / P123 solution to obtain a GeO2 / Si dispersion.
[0051] (2) Preparation of GeO2 / Si@PVA fiber composites:
[0052] 0.5g sucrose was added to the GeO2 / Si dispersion and stirred continuously for 2h on a heated stirrer; 2g PVA was added under strong stirring and stirred continuously for 12h to obtain GeO2 / Si@PVA slurry. The slurry was used as an electrospinning liquid to prepare a GeO2 / Si@PVA fiber composite material.
[0053] (3) Preparation of Ge / Si@CNFs composites:
[0054] The GeO2 / Si@PVA fiber composite material was pre-oxidized at 150°C in air for 2 h, and then carbonized and reduced at 800°C in a hydrogen-argon atmosphere for 6 h (heating rate of 3°C / min) to reduce GeO2 to germanium nanoparticles and convert PVA fibers into carbon fibers to obtain Ge / Si@CNFs composite materials.
[0055] The Ge / Si@CNFs composite material, carbon black and sodium carboxymethyl cellulose were mixed into a slurry in water at a mass ratio of 8:1:1, coated on a copper foil, and dried in vacuum for 12 h to form a slurry with an area of 1.0 cm 2 The electrode disc has an active material loading of about 1.0 mg cm -2 , used as negative electrode material for lithium-ion batteries, half-cells were assembled in a glove box filled with argon, and the lithium storage performance was tested at a constant temperature of 25°C after standing for 24 hours. Cyclic voltammetry curves were recorded in a voltage window of 0.01 to 3 V using an electrochemical workstation. The electrochemical performance of the battery was recorded using a LAND battery test system (LAND CT2001A).
[0056] Figure 1 The X-ray diffraction (XRD) spectrum of the Ge / Si@CNFs composite material prepared in Example 1 shows that the diffraction peaks at 27.3°, 45.3°, 53.7°, 66.0° and 72.8° correspond to the (111), (220), (311), (400) and (331) crystal planes of cubic phase Ge (PDF#04-0545), which indicates that GeO2 has been completely converted into Ge after high temperature treatment under Ar / H2 atmosphere. In addition, in addition to the diffraction peaks corresponding to Ge, other diffraction peaks are also shown in the spectrum, which can well correspond to the standard card of Si (PDF#75-0589).
[0057] Figure 2 This is the Raman spectrum of the Ge / Si@CNFs composite material prepared in Example 1. 1359.6 cm -1 The broad peak at 1600.7 cm corresponds to the structure and defects of the sample (D band), while the -1 The broad peak at corresponds to the layering and topological structure of the sample (G band). The more disordered the carbon material structure is, the higher the defect density is, and the higher the intensity of the D band is. D / I G The ratio is 0.992, while the I D / I G The ratios are 0.906 and 1.001, respectively. This indicates that the addition of Ge leads to an increase in defects in the composite material, making electronic conduction easier and improving the cycle efficiency of the composite material.
[0058] Figure 3This is the thermal decomposition curve of the Ge / Si@CNFs composite material prepared in Example 1. According to calculation, the mass content of carbon is 25.7wt%, and a low proportion of carbon content is beneficial to improving energy density. In the Ge / Si@CNFs composite material, carbon element mainly exists in CNFs, while silicon and germanium are embedded in carbon nanofibers in the form of nanoparticles.
[0059] Figure 4 This is the SEM image of the GeO2 / Si@PVA composite material prepared in Example 1. The GeO2 / Si@PVA composite material presents a very uniform fiber morphology, with a compact and smooth surface and a fiber diameter of 300-400nm.
[0060] Figure 5 This is a SEM image of the Ge / Si@CNFs composite material prepared in Example 1. After pre-oxidation and carbonization treatment, the fiber morphology of the Ge / Si@CNFs composite material remains basically unchanged.
[0061] Figure 6 TEM image of the Ge / Si@CNFs composite material prepared in Example 1. The results show that Si nanoparticles and Ge nanoparticles are well coated by carbon nanofibers. This coating structure can not only improve the structural stability of the material, but also prevent Si and Ge from serious volume expansion and contraction during the charge and discharge process, thereby avoiding the attenuation of battery performance.
[0062] Figure 7 CV curves of the first four cycles of the Ge / Si@CNFs composite electrode prepared in Example 1. + During the first intercalation process of Li x GeO x A reduction reaction occurred. Subsequently, electrolyte decomposition and SEI film formation occurred in the range of 0-0.5 V. In addition, the lithiation process of Ge in the second cycle appeared at about 0.3 V, while the peak at 0.19 V was attributed to the lithiation process of Si. The two oxidation peaks at 0.40 V and 0.52 V corresponded to Li y Si and Li x The delithiation process of Ge. The curves of the third and fourth cycles match well, proving that the electrode has good cycle stability.
[0063] Figure 8 The charge and discharge curves of the Ge / Si@CNFs composite electrode prepared in Example 1. The results show that the discharge and charge platforms of the electrode are similar to Figure 7The positions of the redox peaks in the composite material correspond to those in the charge-discharge process, which further verifies the redox reaction that occurs during the charge-discharge process. The first discharge capacity of the composite material is 3525.6 mAh g -1 and 2353.1mAh g -1 , showing an initial Coulombic efficiency of 66.7%.
[0064] Fig. 9 The Ge / Si@CNFs composite electrode prepared in Example 1 and other comparative electrodes were subjected to 0.2Ag -1 The difference in cycle performance after 200 cycles at different current densities. As can be seen from the figure, the specific discharge capacity of the Ge / Si@CNFs composite electrode is 1152 mAh g -1 , with almost no attenuation after 200 cycles. The excellent lithium storage performance is mainly attributed to the synergy between silicon and germanium, which provide buffer space for each other and effectively alleviate the negative impact of volume expansion during charging and discharging. At the same time, the carbon fiber in the core-shell structure also plays a key role, further alleviating the volume expansion and improving the cycle stability of the material.
[0065] Fig.10 The rate performance of the Ge / Si@CNFs composite electrode prepared in Example 1 at different current densities. -1 At current densities of 1.3 2.0 2.0 2.0 2.5 1.2 1.5 1.6 1.7 1.9 2.1 1.3 1.9 2.3 1.8 1.9 2.1 1.6 1.8 1.9 2.3 ... -1 As the current density increases, the reversible capacity of the Ge / Si@CNFs composite material decreases, but still maintains a relatively high capacity. -1 The reversible capacity of Ge / Si@CNFs composite material reaches 1731.4 mAh g -1 The reversible capacity was well restored, proving that the material has good structural stability and lithium storage reversibility.
[0066] Fig.11 The Ge / Si@CNFs composite electrode prepared in Example 1 was heated to 0.5Ag. -1 The long-term cycling performance at high current density is shown in Figure 2. After 1000 cycles, the discharge capacity of the Ge / Si@CNFs composite material is 764.1 mAh g -1 , and the discharge capacity of the second cycle (1059.7 mAh g -1 ), the capacity retention is 72.1%, which indicates that the Ge / Si@CNFs composite has good long-term cycling stability.
[0067] Comparative Example 1
[0068] The difference from Example 1 is that there is no Ge in the prepared composite material, and the obtained material is recorded as Si@CNFs.
[0069] In the lithium storage performance test, the loading amount of the composite material in the single-piece electrode was 1.0 mg.
[0070] The morphology of Si@CNFs composites is similar to that of Ge / Si@CNFs composites, but their properties are quite different. Fig.12 The results show that the capacity of Si@CNFs composite electrode remains at 386.3 mAh g after 200 cycles. -1 , which is significantly lower than the capacity of the Ge / Si@CNFs composite electrode after 200 cycles, indicating that the addition of germanium helps to improve the lithium storage performance of the Ge / Si@CNFs composite material.
[0071] Example 2
[0072] The difference from Example 1 is that the feed mass ratio of (Ge+Si) to PVA is 0.5:20, and the obtained material is recorded as Ge / Si@CNFs-0.05.
[0073] In the lithium storage performance test, the loading amount of the composite material in the single-piece electrode was 1.0 mg.
[0074] The morphology of Ge / Si@CNFs-0.05 composite material is similar to that of Ge / Si@CNFs composite material, e.g. Fig.13 , but the performance is obviously different. Fig.12 It can be seen that the capacity of the Ge / Si@CNFs-0.05 composite electrode remains at 835.8 mAh g after 200 cycles. -1 , which is significantly lower than the capacity of the Ge / Si@CNFs composite electrode after 200 cycles, further indicating that the addition of germanium has a significant impact on improving the lithium storage performance of the Ge / Si@CNFs composite material.
[0075] Example 3
[0076] The difference from Example 1 is that the mass ratio of (Ge+Si) to PVA is 1.5:20. The prepared material is recorded as Ge / Si@CNFs-0.15.
[0077] In the lithium storage performance test, the loading amount of the composite material in the single-piece electrode was 1.0 mg.
[0078] The morphology of Ge / Si@CNFs-0.15 composite material is similar to that of Ge / Si@CNFs composite material, e.g. Fig.14shown, but the performance is clearly different. Fig.12 It can be seen that the capacity of the Ge / Si@CNFs-0.15 composite electrode remains at 481.6 mAh g after 200 cycles. -1 , which is significantly lower than the capacity of the Ge / Si@CNFs composite electrode after 200 cycles, indicating that too much germanium addition is not conducive to improving the lithium storage performance of the Ge / Si@CNFs composite material.
[0079] Example 4
[0080] The difference from Example 1 is that the mass ratio of (Ge+Si) to PVA is 2:20, and the obtained material is recorded as Ge / Si@CNFs-0.2.
[0081] In the lithium storage performance test, the loading amount of the composite material in the single-piece electrode was 1.0 mg.
[0082] The morphology of Ge / Si@CNFs-0.2 composite material is similar to that of Ge / Si@CNFs composite material, e.g. Fig.15 , but the performance is obviously different. Fig.12 It can be seen that the capacity of the Ge / Si@CNFs-0.2 composite electrode remains at 388.3 mAh g after 200 cycles. -1 , which is significantly lower than the capacity of the Ge / Si@CNFs composite electrode after 200 cycles, indicating that too much germanium addition is not conducive to improving the lithium storage performance of the Ge / Si@CNFs composite material.
[0083] Comparative Example 2
[0084] The difference from Example 1 is that no Si nanoparticles are added, and the obtained material is recorded as Ge@CNFs.
[0085] In the lithium storage performance test, the loading amount of the composite material in the single-piece electrode was 1.0 mg.
[0086] The morphology of Ge@CNFs composites is similar to that of Ge / Si@CNFs composites, e.g. Fig.16 As shown, the performance is quite different. Fig.12 It can be seen that the capacity of the Ge@CNFs composite electrode remains at 333.1 mAh g after 200 cycles. -1 , which is significantly lower than the capacity of the Ge / Si@CNFs composite electrode after 200 cycles.
[0087] Comparative Example 3
[0088] The difference from Example 1 is that no sucrose is added in the preparation of the GeO2 / Si@PVA composite material, and the prepared material is recorded as Ge / Si@C.
[0089] The experimental results show that without the addition of sucrose, the GeO2 / Si@PVA composite material cannot maintain its fiber structure after high-temperature calcination.
[0090] Comparative Example 4
[0091] The difference from Example 1 is that the amount of sucrose added is 1.0 g.
[0092] The experimental results show that the precursor slurry used for GeO2 / Si@PVA composite materials is viscous and cannot be spun.
[0093] In summary, the present invention successfully prepared a Ge / Si@CNFs composite material with a three-dimensional core-shell structure through electrospinning technology. The material exhibited excellent cycle stability and high capacity in the negative electrode of lithium-ion batteries, providing a new method for synthesizing high-performance silicon-carbon negative electrode materials, which is expected to meet the demand for high-performance batteries in commercial equipment such as electric vehicles.
[0094] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a germanium-regulated silicon / carbon fiber composite material, characterized in that: The following steps are involved: Step 1, Preparation of GeO2 / Si dispersion Dissolve F127 in deionized water to prepare F127 solution, add GeO2 polycrystalline particles while stirring, and continue stirring at room temperature for 1 hour to obtain a transparent GeO2 / F127 dispersion; P123 is dissolved in deionized water, and Si nanoparticles are added to the P123 solution to obtain a Si / P123 dispersion; Then, the GeO2 / F127 dispersion is added to the Si / P123 dispersion to obtain a GeO2 / Si dispersion, wherein the molar ratio of Ge to Si is 0.25-2:1; Step 2, preparation of GeO2 / Si@PVA fiber composite material 0.5 g of sucrose was added to the GeO2 / Si dispersion, and then stirred continuously for 2 h on a heated stirrer, and then 2 g of PVA was added under strong stirring, and the mass ratio of sucrose to PVA was ≥ 0.25:1, and then stirred for 12 h to obtain a GeO2 / Si@PVA slurry as an electrospinning liquid, and then electrospinning was performed to obtain a GeO2 / Si@PVA fiber composite material; Step 3, Preparation of Ge / Si@CNFs composites The GeO2 / Si@PVA fiber composite material was pre-oxidized in air at 150°C for 2 h, then carbonized and reduced in a hydrogen-argon atmosphere, and naturally cooled to room temperature to obtain the Ge / Si@CNFs composite material.
2. The method for preparing a germanium-controlled silicon / carbon fiber composite material according to claim 1, characterized in that: The concentration of the F127 solution in step 1 is 4wt%, and the concentration of the P123 solution is 1.5wt%.
3. The method for preparing a germanium-controlled silicon / carbon fiber composite material according to claim 1, characterized in that: The molar ratio of Ge to Si in step 1 is 1:
1.
4. The method for preparing a germanium-controlled silicon / carbon fiber composite material according to claim 1, characterized in that: The mass ratio of (Ge+Si) to PVA in step 2 is 0.5:20-2:
20.
5. The method for preparing a germanium-controlled silicon / carbon fiber composite material according to claim 4, characterized in that: The mass ratio of (Ge+Si) to PVA described in step 2 is 1:
20.
6. The method for preparing a germanium-controlled silicon / carbon fiber composite material according to claim 1, characterized in that: In step 3, the heating rate of carbonization in a hydrogen-argon atmosphere is 3°C / min, the carbonization temperature is 800°C, and the reduction time is 6h.
7. The germanium-regulated silicon / carbon fiber composite material prepared by the preparation method according to claim 1, characterized in that: The invention comprises silicon nanoparticles, germanium nanoparticles and a carbon fiber matrix, wherein the silicon nanoparticles and the germanium nanoparticles are evenly distributed in the carbon fiber matrix to form a three-dimensional network core-shell structure.
8. Use of the Ge / Si@CNFs composite material according to claim 7 as a negative electrode material in a lithium ion battery.
Citation Information
Patent Citations
Preparation method of cathode material of germanium-mesoporous carbon fiber composite lithium battery
CN104779378A
Reticular silicon / graphite composite material of lithium battery and preparation method thereof
CN106571454A
Silicon-based heterostructure material and preparation and application thereof
CN114649533A
Silicon based carbon nanofiber composite containing silicon or silicon oxide, manufacturing method of silicon, and lithium secondary battery including composite
KR101348200B1